2021
DOI: 10.1007/s40122-021-00293-6
|View full text |Cite
|
Sign up to set email alerts
|

Decompression Using Minimally Invasive Surgery for Lumbar Spinal Stenosis Associated with Degenerative Spondylolisthesis: A Review

Abstract: Lumbar spinal stenosis (LSS), which often occurs concurrently with degenerative spondylolisthesis (DS), is a common disease in the elderly population, affecting the quality of life of aged people significantly. Notwithstanding the frequently good effect of conservative therapy on LSS, a minority of the patients ultimately require surgery. Surgery for LSS aims to decompress the narrowed spinal canals with preservation of spinal stability. Traditional open surgery, either pure decompression or decompression with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 128 publications
0
22
0
1
Order By: Relevance
“…However, this technique has some disadvantages, such as high surgical risk, use of general anesthesia, greater trauma, high blood loss, long hospital stay, destruction of the rear stable structure, and the risk of severe complications, which seriously affect the clinical treatment effect. 8 , 19 , 20 One study found that patients with spinal instability during open decompression surgery had a high revision rate of 21%. 21 Minimally invasive surgeries, such as PELD, have the advantages of less trauma, less bleeding, faster recovery, shorter hospital stay, and significant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique has some disadvantages, such as high surgical risk, use of general anesthesia, greater trauma, high blood loss, long hospital stay, destruction of the rear stable structure, and the risk of severe complications, which seriously affect the clinical treatment effect. 8 , 19 , 20 One study found that patients with spinal instability during open decompression surgery had a high revision rate of 21%. 21 Minimally invasive surgeries, such as PELD, have the advantages of less trauma, less bleeding, faster recovery, shorter hospital stay, and significant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 20 patients with spinal stenosis, five patients recommended for conservative treatment by the three neurosurgeons in the study after having viewed their conventional MRI spinal images were reclassified by all three neurosurgeons in the study as appropriate for decompressive surgery after viewing an MRI showing the same patients with the axial load associated with standing [9] (see Figure 1). The improvement in surgical tools has allowed for the development and expansion of minimally invasive spine surgery such as indirect decompression through the use of devices between the interspinous processes, microscopic spine surgery, and endoscopic procedures [10]. These new techniques offer less injury to tissue, lower rates of complications, and reduced recovery times.…”
Section: Review Clinical Presentation Of Lbpmentioning
confidence: 99%
“…These new techniques offer less injury to tissue, lower rates of complications, and reduced recovery times. It may even be expected that minimally invasive spine surgery will replace conventional open surgery in the near future [10].…”
Section: Review Clinical Presentation Of Lbpmentioning
confidence: 99%
“…Nevertheless, traditional open surgery is more invasive and often leaves intractable lower back pain secondary to spinal instability, epidural scarring, and adjacent segmental degeneration after surgery [10]. Minimally invasive is a hot topic and trend in spinal surgery [11,12]. In recent years, percutaneous spinal endoscopic techniques have emerged with the interlaminar Endoscopic Surgical System iLESSYS ® Delta system, which includes a wider diameter and shorter length of working cannula, which have greatly improved in terms of visualization, working space, safety, and efficiency [13][14][15].…”
Section: Introductionmentioning
confidence: 99%